A phenomenological explication of the male alcoholic's experience of existence with mother and father - Singer, Stanley (Rhodes University, Faculty of Humanities, Department of Psychology, 1984)
Much is written, especially in psychodynamically oriented literature, about the unduly close dependency relationship male alcoholics have with their mothers. Whilst not disputing this it became apparent to myself when working with them that they also expressed strong attachments to their fathers who were described as absent or punitive. The literature goes on to theorize that a repressed homosexual element is often at work in the male alcoholic. Not much more of substance is said about the father other than he may be absent or punitive - even less is mentioned of the male alcoholic's experience with his father. It appears that this relationship has remained largely unexplored as a result of an uncritical imposition of theory, especially psychodynamic, upon the complex phenomenon of alcoholism. These theories generally posit the mother's influence over all problems in living be they neuroses, psychoses or alcoholism. It is possible that a dialogue exists between mother, father and alcoholic son which is more extensive and complex than that currently described in the literature, with father playing a greater role than previously believed.
Keywords: Alcoholism -- Psychological aspects